Ministry of reconciliation in the context of ethnic ideology and genocide : a theological evaluation of the Presbyterian Church in Rwanda - Muke, Nagaju (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.